Pharmaceutical Quality Control and Assurance in the 21st Century - Dandekar, Mayur R. (Asian Journal of Pharmaceutics (AJP), 2024)
In the 21st century, the pharmaceutical industry faces dynamic and ever-evolving challenges that demand a robust commitment to quality control and assurance. This review article delves into the multifaceted landscape of pharmaceutical quality, highlighting plays’ critical role in ensuring medication safety and efficacy. As the pharmaceutical world experiences profound shifts driven by technological advertisement, global supply chains, and regulatory updates this article offers an in-depth exploration of the key facets that define quality control and assurance in this era. Regulatory oversight has significantly transformed, with agencies such as the FDA and EMA adapting to keep pace with the industry’s changing dynamics. We examine the current regulatory landscape, its impact on quality standards, and the growing emphasis on transparency and compliance. Advertisements in analytical techniques have revolutionized quality control, from mass spectrometry and nuclear magnetic resonance to sophisticated spectroscopy methods. This article explores these advanced tools and their contribution to product quality. Quality by design (QbD) principles have gained traction, advocating a proactive approach to quality control by integrating it into the product development process. We discuss the implications of QbD and its tangible benefits. Looking to the future, we predict emerging trends that will continue to shape pharmaceutical quality control and assurance technology such as blockchain and 3D printing are expected to play pivotal roles. In conclusion, this comprehensive review serves as a vital resource for professionals, researchers, and playmakers seeking a nuanced understanding of the ever-evolving terrain of pharmaceutical quality control and assurance. It emphasizes the critical importance of adapting to meet modern challenges and seizing opportunities for innovation in the pursuit of pharmaceutical excellence.